LOKAKARYA KEPEMIMPINAN SEKOLAH (PENGAMBILAN KEP`UTUSAN BERDAMPAK) PADA SEKOLAH PENGGERAK DI KABUPATEN TEGAL - Meilina Haris Mayekti; Dinar Faiza (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
The driving school is one of the government programs aimed at realizing Indonesia's educational vision to achieve a sovereign, independent, and dignified Indonesia through the Pancasila student profile. The goal of the Sekolah Penggerak program is to improve literacy, numeracy, and student character in Indonesia, as well as to enhance the capacity of school principals and teachers to promote quality learning. Therefore, efforts need to be made to improve the quality of human resources among supervisors, principals, and teachers. One such effort is through workshops. These workshops are specifically designed for the driving school program. The aim of these workshops is to enhance impactful decision-making skills. This activity uses the Participatory Action Research (PAR) method, which involves full participation and engagement to ensure contributions from one party to another, facilitating change and improvement. This community service activity will also result in a document outlining steps for impactful decision-making.